O ensino de escrita em um livro didático do ensino médio - AIRES, Diana Costa (2023)
The teaching of writing receives great attention in Portuguese classes since Elementary School. However, evidence such as the ENEM reveals that this teaching still presents many problems. For this reason, the present research aimed to investigate the writing teaching practices proposed by a Portuguese Language textbook offered in Public High School institutions. In order to proceed to the analysis, we take as the north what Antunes (2003) presents about writing practice in school. According to Antunes (ibid), a writing teaching that considers the interationalist view of language must be organized in such a way that it is seen on a writing of texts: a) also authored by the students; b) socially relevant; c) functionally diversified; d) that they have readers; e) contextually appropriate; f) methodologically adjusted; g) oriented towards global coherence; h) also adequate in its presentation. In this study we analyzed only one chapter for the production of text of an LD in view of the great similarity that the chapters have with each other as regards the organization and structuring. The careful observation of the treated chapter allowed one to perceive some care with writing: at no time did the authors approach it in a mechanical way, on the contrary, presented and discussed new models and forms of production. The preoccupation with the organization and presentation of the written text was also perceived, this concern can be identified through the number of chapters dedicated to textual production (11).